Principles of aeroelasticity - Bisplinghoff, Raymond L.; Ashley, Holt (Dover Publications, 1975)
Two revered pioneers of aerospace engineering follow up their earlier volume on aeroelasticity with this mini-handbook on the principles of elasticity. While geared toward professional engineers, this volume will be helpful for students as well. Topics include methods of constructing static and dynamic equations, heated elastic solids, forms of aerodynamic operators, structural operators, and more.
Keywords: Aeroelasticity.; elektronické knihy; electronic books